Skeletal component counts of sediments from the reef island Langkai, Spermonde Archipelago, Indonesia - Kappelmann, Yannis; Sengupta, Meghna; Mann, Thomas; Stuhr, Marleen; Kneer, Dominik; Jompa, Jamaluddin; Westphal, Hildegard (In: Kappelmann, Y et al. (2024): Sedimentological and remote sensing data from the reef island Langkai, Spermonde Archipelago, Indonesia [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.967719, 2024)
The data set includes facies compositions of sediments from the reef island Langkai, SW Sulawesi, Indonesia. The data was collected in order to reconstruct the Holocene and modern (sediment) dynamics over the past ca 6,000 years. Sediment samples were obtained from sediment cores taken by percussion drilling and hand-held (Auger) coring in May 2016 and July 2021. Laboratory analysis of the sediments and shoreline analysis were carried out between 2021 and 2023. The skeletal components of the grain size fractions >2 mm, 2-1 mm, 1-0.5 mm and 0.5-0.25 mm were analyzed under a digital microscope by point counting. A total of n=100 skeletal components were identified from each fraction.
Keywords: Carbonate Sedimentology; Facies; Grain Size; Holocene; Radiocarbon age; Southeast Asia; Spermonde Archipelago